2011
DOI: 10.1586/eci.11.18
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and susceptibility to autoimmune diseases

Abstract: For decades, obesity has been considered to be the result of the complex interaction between genes and the environment and its pathogenesis is still unresolved. The discovery of hormones and neural mediators responsible for the control of food intake and metabolism at the hypothalamic level has provided fundamental insights into the complicated pathways that control food intake. However, the molecular basis for the association between obesity and low-degree chronic inflammation is still unknown. More recently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 82 publications
2
62
0
2
Order By: Relevance
“…There are strong pieces of evidence suggesting that obesity is an independent risk factor for psoriasis [113] . Furthermore, it has been indicated that obesity is more prevalent in patients with severe psoriasis than in patients with the mild form, reinforcing the link between body fat mass and psoriasis [3] . Extensive data, acquired on the proinflammatory role of adipocytes, show the pathogenic role of obesity in the incidence of psoriasis and in its severity.…”
Section: Obesity and Psoriasismentioning
confidence: 97%
“…There are strong pieces of evidence suggesting that obesity is an independent risk factor for psoriasis [113] . Furthermore, it has been indicated that obesity is more prevalent in patients with severe psoriasis than in patients with the mild form, reinforcing the link between body fat mass and psoriasis [3] . Extensive data, acquired on the proinflammatory role of adipocytes, show the pathogenic role of obesity in the incidence of psoriasis and in its severity.…”
Section: Obesity and Psoriasismentioning
confidence: 97%
“…A causal link between obesity and thyroid autoimmunity has not been established so far, yet observational data from the general population suggest that obesity may increase the risk of developing allergies and several autoimmune diseases (111,112), possibly through the chronic pro-inflammatory status resulting from the accumulation of WAT in the obese patients. In obesity, the immunological tolerance can be affected both directly and indirectly, via an altered secretion of adipokines (predominantly leptin, adiponectin, and visfatin) and/or cytokines (interleukin 6 (IL6), tumor necrosis factor alpha, and interleukin 10 (IL10)).…”
Section: Obesity and Thyroid Autoimmunitymentioning
confidence: 99%
“…In obesity, the immunological tolerance can be affected both directly and indirectly, via an altered secretion of adipokines (predominantly leptin, adiponectin, and visfatin) and/or cytokines (interleukin 6 (IL6), tumor necrosis factor alpha, and interleukin 10 (IL10)). The final result would be a shift from Th2 to Th1 immune response; the latter being more prone to produce autoimmune reactions (112,113,114). The visceral adipose tissue (VAT) contains resident macrophages, endothelial cells, and T cells with biased T cell receptors, which may contribute to mount an immune response by producing excessive amounts of pro-inflammatory cytokines (115).…”
Section: Obesity and Thyroid Autoimmunitymentioning
confidence: 99%
“…Also, miRNA expression has been seen to show sex differences, providing yet another potential avenue for sex differences (reviewed in Dai and Ahmed (2014)). Associations between AITDs and type 2 diabetes (Coller andHuggins, 1927 andProcaccini et al, 2011) and suggestions that inflammation may be at the core of both and responsible for the sex differences in incidence (Thorand et al, 2007).…”
Section: Introductionmentioning
confidence: 99%